2005
DOI: 10.1007/s00210-005-1061-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carticaine on the sarcoplasmic reticulum Ca2+-adenosine triphosphatase. II. Cations dependence

Abstract: Ca2+-ATPase is a major intrinsic protein in the sarcoplasmic reticulum (SR) from skeletal muscles. It actively transports Ca2+ from the cytoplasm to the SR lumen, reducing cytoplasmic [Ca2+] to promote muscle relaxation. Carticaine is a local anesthetic widely used in operative dentistry. We previously showed that carticaine inhibits SR Ca2+-ATPase activity and the coupled Ca(2+) uptake by isolated SR vesicles, and increases the rate of Ca2+ efflux from preloaded vesicles. We also found that these effects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Hydrophobic drugs inhibit CaATPase (Sokolove et al, 1986;Michelangeli et al, 1990;MartinezAzorin et al, 1992;Caravaca et al, 1995;Takara et al, 2000Takara et al, , 2005. Here we report that lidocaine and bupivacaine inhibited the CaATPase activity in sarcoplasmic reticulum membranes from masseter and medial pterygoid muscles.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Hydrophobic drugs inhibit CaATPase (Sokolove et al, 1986;Michelangeli et al, 1990;MartinezAzorin et al, 1992;Caravaca et al, 1995;Takara et al, 2000Takara et al, , 2005. Here we report that lidocaine and bupivacaine inhibited the CaATPase activity in sarcoplasmic reticulum membranes from masseter and medial pterygoid muscles.…”
Section: Discussionsupporting
confidence: 51%
“…K i values were higher for Ca uptake than for enzymatic activ ity. Here we must consider that CaATPase activity was measured in the presence of calcimycin and calcium uptake in its absence, and that the relative distributions of the intermediate species of the cycle during the steady state of the reactions were different under both conditions (Takara et al, 2005). Because the enzyme undergoes conformational changes along the cycle, one could expect that any inhibitor displays different affinities for the differ ent enzymatic conformations, and therefore, any change in the relative distributions of the conformers must affect the K i (app) of the inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,41,43 A surge in myoblastic apoptosis is the sequela of LA exposure. 1,19e23,25e29 Apoptosis is triggered by increased Back muscles, 37 back leg muscles, 43 breast muscle, 28 C2C12 cell line, 18e23,25,26 oesophageal muscle, 24 extensor digitorum longus muscle, 1,24,35,36 first lumbrical of foot muscle, 27 flexor digitorum brevis muscle, 24 hind leg muscles 15,32,33,42 masseter muscle, 34,37,41 medial pterygoid, 37,38,41 psoas muscle 40 quadriceps muscle, 29 skeletal muscle, 13,30,31 soleus muscle, 1,24 temporalis muscle, 39 tibialis anterior muscle 1 Humans, 13,29 mice, 1,18e26,35,36 quail, 28 rats, 27 pigs, 42 rabbits 15,30e34,37e41,43 Articaine, 38 benzocaine, 32 bupivacaine, 1,13,18e21,23e29,34,35,41e43 bupivacaine S and R enantiomers, 35,36 bupivacaine with caffeine, 1 bupivacaine with dantrolene, 1 bupivacaine with microspheres, 22 carticaine,…”
Section: Myotoxic Damagementioning
confidence: 99%
“…The functional aspects of SERCA, such as structure , enzymatic activity, modulation of calcium transport, binding and efflux, and phosphorylation by ATP and inorganic phosphate (Pi) , as well as the effects of different drugs and cations , have been studied in detail in sarcoplasmic reticulum (SR) membranes isolated from fast‐twitch skeletal muscles. However, few authors have reported on SERCA isolated from masticatory muscles .…”
mentioning
confidence: 99%